Rule-Based Algorithms for Automatic Pronunciation of Portuguese Verbal Inflections - Marquiafavel, Vanessa [UNESP]; Shulby, Christopher; Veiga, Arlindo; Proenca, Jorge; Candeias, Sara; Perdigao, Fernando; Baptista, J.; Mamede, N.; Candeias, S.; Paraboni, I; Pardo, TAS; Nunes, MDV (Springer, 2014)
The correct automatic pronunciation of words is a nontrivial problem, even for inflexions of Portuguese verbs, and has not been systematically solved yet, if verbal irregularity is taken into account. The purpose of this work is to enhance a grapheme-to-phoneme system with a verb pronunciation system for both varieties of Portuguese, Brazilian (BP) and European (EP), given only its infinitive form. The most common verbs for BP and EP (1000 and 2600 respectively) constituted our database to test the pronunciation system. A detailed and systematic analysis of regular and non-regular pronunciation forms of the inflected verbs was performed, and an index of irregularity for verb pronunciation is proposed. A rule-based algorithm to pronounce all inflexions according to verb paradigms is also described. The defined paradigms are, with a high level of certainty, representative of all the verbs for Portuguese.
Keywords: Brazilian Portuguese; European Portuguese; Verbs; Pronunciation; Rule-based algorithms